The influence of entrepreneurship in youth unemployment in transition and MENA countries - Sulejman, Rejhan (Array, 2020)
Even though young people do not have enough work experience and skills, there is no doubt that they are an important source of the economic growth. However, the integration of young individuals to the labor market faces difficulties because of the missing experience, so one of the tools used to integrate them easily in the market has been entrepreneurship. In the last decade the concept ‘entrepreneurship’ and ‘entrepreneur’ have become very popular especially among youth. Studies show that young people are becoming interested in start-up businesses because they think about what they can do for themselves instead of what the government can do for them. The aim of this paper is to identify the relationship of entrepreneurship with youth unemployment in transition and Middle East and North Africa (MENA) countries for the period 2008 – 2016. An econometric analysis of panel data for the 33 countries is executed in Stata 12, to identify whether entrepreneurship can be used as a tool to decrease youth unemployment. There is no universal method to measure entrepreneurship, so data collected from different countries can bring incorrect results. In order to avoid incorrectness and misleading results we use TEA (total-early stage entrepreneurial activity) for entrepreneurship, from the Global Entrepreneurship Monitor, which uses the same methodology for data collection in every country. This study proves the theories from the literature review stating that young people have ambitions and are interested in starting their own business.